Pengaruh Dosis Batuan Fosfat Dan Dolomit Terhadap Pertumbuhan Dan Hasil Kacang Tanah (Arachis Hypogaea L) Kultivar Tuban - Arlingga Ichwan Maulana; Alfandi Alfandi; Siti Wahyuni (Program Studi Ilmu Pertanian Pascasarjana UGJ, 2017)
The purpose of this research was to know the interaction effect from rock phosphate and dolomit rate to growth and yield of groundnut (Arachis hypogaea L.) cv. Tuban and to know relationship between growth and yield component of groundnut plant (Arachis hypogaea L.) cv. Tuban. This research was conducted at Candrajaya Village, Sukahaji Sub-District, Majalengka Regency- West Java, Indonesia from April until July 2015. This research was arranged by Completely Randomized Block Design Factorial, with two factors and repeated three times. First factor is rock phosphate rate with four levels (0, 150, 250, 350 kg ha-1) per plots. Second factor is dolomite rate with three levels (0, 300, 500 kg ha-1). The result showed that rock phosphate rate gave significantly effect to number of leaves at 28 DAP, number of productive branches, root volume, number of dry pods per crop, number of filling pods, weight of dry pod per plant, number of seeds, weight of dry seeds per plant and weight of dry seeds per plot. Dolomite rate gave significantly effect to number of branches at 28 DAP and number of productive branches. There were interaction between rock phosphate and dolomit to plant height at 28 Days After Planted (DAP) and weight of dry pods per plot. Number of leaves 21 DAP and 28 DAP were positively correlated to weight of dry seeds per plot.